Development of Microwave Maceration Method for the Extraction of Organic Constituents of Buton Bajakah (Kakatola) Root and Test of its Activity as an Antioxidant - Imran, Imran; Alwahab, Alwahab (Advance Sustainable Science, Engineering and Technology, 2024)
The extraction of organic constituents, antioxidant activity test, and toxicity test of Bajakah Buton (Kakatola) root extract were conducted. Bajakah Buton roots were extracted using the microwave-assisted maceration method, followed by extraction using ethyl acetate solvent. The resulting yield reached 40,827% b/v. The analysis identified the presence of flavonoids, glycosides, phenols, terpenoids, and tannins. Antioxidant activity testing using the DPPH method showed IC50 values of ethyl acetate extract and vitamin C of 100.317 ppm and 13,797 ppm, respectively, indicating strong antioxidant properties. Toxicity tests using the BSLT method showed that the ethyl acetate extract of Bajakah Buton roots had a toxic activity with an LC50 value of 11,232 ppm. The results of this study will continue to be developed, so it is expected to be an important breakthrough in the field of cancer treatment.